2022
DOI: 10.1097/bpo.0000000000002258
|View full text |Cite
|
Sign up to set email alerts
|

Appropriate Surgical Timing of Salter Innominate Osteotomy for Residual Acetabular Dysplasia in Children

Abstract: Background: Salter innominate osteotomy (SIO) provides favorable results for treating residual acetabular dysplasia in young children. In this study, we examined the midterm results of SIO according to the age at surgery to determine the optimal timing of this procedure. Methods: We retrospectively examined 50 hips of 42 patients (8 boys and 34 girls) with acetabular dysplasia who underwent SIO and were followed up until skeletal maturity. The centeredge angle (CEA) was measured based on the anteroposterior ra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 26 publications
0
8
0
Order By: Relevance
“…Primary approach to DDH remains controversial between 18 to 24 months. [9] Majority of DDH cases are females, approximately 75%-82% of all DDH cases in recent studies [8,14,16]. Moreover, Gurger et al found all their cases to be female [15].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Primary approach to DDH remains controversial between 18 to 24 months. [9] Majority of DDH cases are females, approximately 75%-82% of all DDH cases in recent studies [8,14,16]. Moreover, Gurger et al found all their cases to be female [15].…”
Section: Discussionmentioning
confidence: 99%
“…In different studies, DDH has been treated in a wide age range from 10 months to 11.4 years. [11][12][13][14] Between 6 to 18 months, CR is the treatment choice and OR is only performed in unsuccessful CRs. Pelvic osteotomy is generally used in over 24 months cases.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Salter osteotomy is a classic method of pelvic osteotomy, which belongs to the osteotomies that change the direction of the acetabulum. It was first proposed by Salter in 1961[ 52 ]. The osteotomy line of Salter is from the anterior inferior iliac spine to the great ischial notch, and the entire acetabulum is turned forward and outward with the pubic symphysis as the fulcrum.…”
Section: Redirectional Osteotomymentioning
confidence: 99%
“…It changes the overall orientation of the acetabulum to increase the inclusiveness of the acetabulum to the femoral head, and the shape and volume of the acetabulum remain unchanged[ 3 ]. Therefore, Salter osteotomy is suitable for the following[ 52 , 53 ]: (1) Children aged 18 mo to 6 years with unossified pubic symphysis; (2) anterolateral acetabular defect as the main defect; and (3) AI is basically normal. Salter osteotomy requires internal fixation support, so the wedge-shaped bone removed from the ilium is placed into the fracture line and fixed with Kirschner wire to increase stability of the acetabulum after osteotomy.…”
Section: Redirectional Osteotomymentioning
confidence: 99%